Reliability maintenance and logistic support a life cycle approach - Kumar, U. Dinesh; Crocker, John; Knezevic, J.; El-Haram, M. (Kluwer Academic, 2000)
Reliability, Maintainability, and Supportability play a crucial role in achieving a competitive product. While manufacturing costs are important for the success of a product, they are not the sole domains in realizing its competitive edge. Improved manufacturing and operating quality and performance coupled with reduced acquisition cost and in-service cost of ownership are important in achieving business success. It is the early phase of design which offers the greatest opportunity to address these requirements, and thus create life cycle effectiveness. The main objective of Reliability, Maintenance and Logistic Support - A Life Cycle Approach is to provide an integrated approach to reliability, maintainability, maintenance and logistic support analysis. We not only look at the ways we can improve the design process to ensure the product offers value for money, but we also consider how the owners can get the most from these products once they have entered service. The approach provides a meaningful way of integrating reliability, maintenance and supportability to enhance the product performance and sales opportunities.